CONSEQUENCES OF COVID-19 PANDEMIC ON PLACEMENT OF CONSUMER PRODUCTS ON THE GLOBAL MARKET AND THE MARKET OF THE REPUBLIC OF SERBIA - Marić, Radenko; Đurković Marić, Tijana (International Journal of Economic Practice and Policy, 2021)
The COVID-19 pandemic declared by the World Health Organization (WHO) on March 11, 2020, caused unimaginable shocks on the demand side, especially with consumer goods (Fast-Moving-Consumer-Goods - FMCG). Anti-pandemic measures such as lockdown policy, reduced contacts, and keeping physical distance have caused the accumulation of basic food, a decline in demand for secondary products, and an increase in the share of electronic retail. In this regard, this paper aims to project the placement of consumer products during the COVID-19 pandemic on the market of the Republic of Serbia. The research will include a comparison of the situation on the domestic market in 2019, that is, the period preceding the pandemic, with the period March-August 2020. Based on two possible scenarios for the end of the COVID-19 pandemic, a projection of domicile GDP and sales volume of consumer products is going to be performed. The results of the research will indicate to trade policymakers and competent institutions what measures need to be taken for the revenue and profitability of the retail sector to reach the level they achieved in the period before the pandemic. The paper also presents suggestions for future research related to the subject matter.